Mood and coping in clinically isolated syndrome and multiple sclerosis. (30th October 2013) - Bianchi, V.; De Giglio, L.; Prosperini, L.; Mancinelli, C.; De Angelis, F.; Barletta, V.; Pozzilli, C.
<x xml:space="preserve">Abstract</x> Objective Few studies have examined behavioural changes in the early phase of multiple sclerosis (MS). The aim of the study is to investigate mood alterations and to explore coping strategies regarding patients with clinically isolated syndrome (CIS) and relapsing‐remitting MS (RRMS). Materials and Methods The communication of diagnosis was made by one neurologist using a standardized approach. Depression, anxiety and coping questionnaires were filled in within 1 month from the diagnosis and at 3, 6, 12, 18 and 24 months subsequently. Results Thirty‐nine patients were examined (11 CIS, 28 RRMS), also 39 healthy controls. At entry, patients showed a lower degree of hostile behaviour and a higher level of depression than the controls. At follow‐up, a reduction in depression, anxiety and a better coping adjustment was observed. A higher reliance on 'Accepting responsibilities' coping score was seen in patients with higher levels of depression and anxiety. No significant differences were revealed by group comparisons between CIS and RRMS. Conclusions This study highlights transient mood alterations and an improving of adaptive coping over a period of time in patients with CIS and RRMS. Similar emotional reactions and coping in clinical subgroups suggest that these factors are independent from the type of information provided during the communication of the diagnosis.